IMPLEMENTING DEADLINE LEARNING STRATEGY TO IMPROVE STUDENTS' INTEGRATED SCIENCE LEARNING OUTCOMES - Kartini Br. Sembiring (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
The purpose of this research was to improve the students’ learning outcomes on integrated science subject of class VIII.1 SMP Negeri 2 Bangko Kabupaten Rokan Hilir Regency by implementing the active learning of Deadline strategy. The subjects of this study were 30 students of Class VIII.1 SMP Negeri 2 Bangko Kabupaten Rokan Hilir. The research was a classroom action research. Based on the results of the study, the average score of the students’ learning outcomes before the implementation of Deadline strategy was only 62.50 with the percentage of learning mastery of 36.7%. it was found that the average score of the students’ learning outcomes in the first cycle was 67.33 with the the percentage of learning mastery of 66.7%. this meant that 20 students obtained a minimum score of 65 (KKM). Then, after reflection and improvements to learning weaknesses, the average score of students’ learning outcomes in the second cycle reached 82.33 with 100% learning mastery. This indicated that all students reached the specified KKM, so the implemnentation of Deadline Strategy successfully improved students’ learning outcomes.